Sustaining Tolerance According To Brenda Almond's "Education For Tolerance": An Analysis From Islamic Perspective - Mohd Faizal, A.K; Muhammad Syahid, Ahmad; Mohd. Khairul Nizam Zainan Nazri (IOSR Journal, 2024)
Volume 20, Issue 8 (Page: 46-50)